Annotated record of the detailed examination of Mn deposits from CNAV Endeavour in 1967 to 1968 over the Bowie Seamount area - Richard Howard Herzer (PANGAEA, 1970)
Bowie Seamount, a submerged volcano situated off the west coast of Canada at 53° 18; N, 135° 39 extquotesingle W, has a relief of 10,000 ft. and comes to within 100 ft. of the ocean surface. It is made up of a series of intersecting ridges which together give the mountain an overall northeast - southwest elongation. It appears to be a combination central and fissure type volcano which has been built up over a system of intersecting fractures in the oceanic crust. Two terraces form the flattened summit of the volcano at approximate depths of 45 and 130 fathoms. These are thought to be the remains of platforms produced by combined wave erosion and shallow-water vulcanism during late Quaternary time when sea level was lower than it is today. The last phase of volcanic activity on the summit occurred after the formation of the upper terrace no more than 18,000 years ago. Samples dredged from the upper half of the volcano include: pillow fragments, fragments of non-pillowed flows, pillow breccias, bombs, tuffs, ash, and unsorted tephra. The rocks are mainly alkali olivine basalts, accompanied by rare andesites which, presumably, were derived by differentiation of the basaltic magma. Feldspathic and gabbroic inclusions, many of which appear to be cumulates, are common in the basalt. Ice-rafted rocks are rare on the summit of Bowie Seampunt but are common on its nearest neighbour - Hodgkins Seamount. A ferro-manganese deposit, apparently over 1 million years old, that exists on the summit of Hodgkins Seamount, suggests that this peak is relatively much older than the summit area of Bowie Seamount. Palagonite appears to form as the initial phase of weathering of glassy basalts in the area of study but the products of more advanced weathering are montraorillonite and zeolites. Rock fragments that have been rounded by chemical weathering are common.
Supplement to: Herzer, RH (1970): A geological reconnaissance of Bowie Seamount (MS thesis). University of British Columbia, Vancouver, Canada, 112 pp, https://open.library.ubc.ca/cIRcle/collections/831/items/1.0053140